Development of trade blocs in an era of globalization: Proximity still matters - Aleid Brouwer; Tristan Kohl (European Regional Science Association (ERSA), 2011)
This article describes the development of international trade blocs world wide from the 1950s till 2010. We updated the data on international trade flows and introduced a new trade bloc variable based on the intramax hierarchical clustering technique, which defines trade blocs on actual trade intensities and not - as was preciously done - by traditional geographic and political factors: such as the division into a triad of economic regions based on North America, the European Union and Japan. Nevertheless, the results of intramax hierarchical clustering indicate that actual trade flows are very much influenced by geographical and political factors; after all, proximity matters. To explain how mechanism of globalization changed trade patterns over the last half century and how - in the end - proximity is one of the most explanatory variables - we furthermore apply multivariate analysis with gravity-model based variables aims to explain which geographical, political and cultural factors do contribute to the (importance of) proximity in trade partners. In addition we also apply GIS to analyze patterns and proximity issues.
Keywords: 330